If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Simplifying 5y + -3 = 2y + 9 Reorder the terms: -3 + 5y = 2y + 9 Reorder the terms: -3 + 5y = 9 + 2y Solving -3 + 5y = 9 + 2y Solving for variable 'y'. Move all terms containing y to the left, all other terms to the right. Add '-2y' to each side of the equation. -3 + 5y + -2y = 9 + 2y + -2y Combine like terms: 5y + -2y = 3y -3 + 3y = 9 + 2y + -2y Combine like terms: 2y + -2y = 0 -3 + 3y = 9 + 0 -3 + 3y = 9 Add '3' to each side of the equation. -3 + 3 + 3y = 9 + 3 Combine like terms: -3 + 3 = 0 0 + 3y = 9 + 3 3y = 9 + 3 Combine like terms: 9 + 3 = 12 3y = 12 Divide each side by '3'. y = 4 Simplifying y = 4

| 6x+4(3x-2)=4(4x-1)-6 | | x^3=-19x^2+42x | | (x+4)=7(x-2) | | 4c^3+4c^2-48c=0 | | 5x^2+10x-1=0 | | x-7=-5 | | 13(4y+11)=7+5(11y+9) | | 60-4x=4x | | x^2-5x=50 | | 2(x-8)+x=3(x-9)+11 | | -x^2+11x+5=0 | | 3b^3-8b^2-3b=0 | | 5x-4x+9=0 | | x^2+4x+3=4 | | 18z^3=15z^2+12z | | 0.4(4+x).10=60 | | 12a^3=16a^2+3a | | X-19=6-4x | | 5(8x+1)+13x=6(9x-4) | | 4(4+x)*10=60 | | x^2-9x=36 | | 2y^2=98 | | 4x^2-12x+36=0 | | -6x^2-11x-4=0 | | 12-7x=60-35x | | 4x^2=9 | | 6x^2-11x+4=0 | | 22+5y+7=2+9y-5 | | 49c^2=81 | | 14(25a+19)=34a-(15a-29)+18 | | 4y^3-36y=0 | | -12x^2+5x+2=0 | | 3x^4-48x^2=0 | | x^2+3x+8=5 | | -x^2=2x-99 | | -x^2+16x=63 | | 0.2(x+3)=0.2+3(0.1-x) | | 3x^5+27x^4+54x^3= | | 3+8c=35 | | 13+3d=-8 | | 6a^2-12-4a=19a-32 | | -121r^2+1= | | 4p-p-p-p-p+2p= | | 2x-8(3-x)=5 | | X^3+8x^2+x+8= | | 2b^3+16b^2=-30b | | 35x^2+66x+27= | | 3a-y=4+a | | X^2+26x+5= | | -7x+4=5x+12 | | x^2+5x+3=9 | | -15x-187=101+x | | 6y^3-4y^2-42y= | | -17x-18=14-18x | | -115=5(4x-7) | | -328=x-7(4-7x) | | 3r^2+16r+5= | | 113=5x+2(6x-3) | | 3x+4y=23 | | -102=4(7r+4) | | -2.17=0.35r | | 6+10x=33+x | | 5g=12 | | 1+1+1+1+1+1+1+1+1= | | 5x+10=91-4x |